Comparative Analyses of Chloroplast Genomes From 14 Zanthoxylum Species: Identification of Variable DNA Markers and Phylogenetic Relationships Within the Genus - Zhao, Kaihui; Li, Lianqiang; Quan, Hong; Yang, Junbo; Zhang, Zhirong; Liao, Zhihua; Lan, Xiaozhong (Frontiers in Plant Science, 2021)
Zanthoxylum L. is an economic crop with a long history of cultivation and domestication and has important economic, ecological, and medicinal value. To solve the classification problems caused by the similar morphological characteristics of Zanthoxylum and establish a credible phylogenetic relationship, we sequenced and annotated six Zanthoxylum chloroplast (cp) genomes (Z. piasezkii, Z. armatum, Z. motuoense, Z. oxyphyllum, Z. multijugum, and Z. calcicola) and combined them with previously published genomes for the Zanthoxylum species. We used bioinformatics methods to analyze the genomic characteristics, contraction, and expansion of inverted repeat (IR) regions; differences in simple sequence repeats (SSRs) and long repeat sequences; species pairwise Ka/Ks ratios; divergence hotspots; and phylogenetic relationships of the 14 Zanthoxylum species. The results revealed that cp genomes of Zanthoxylum range in size from 158,071 to 158,963 bp and contain 87 protein-coding, 37 tRNA, and 8 rRNA genes. Seven mutational hotspots were identified as candidate DNA barcode sequences to distinguish Zanthoxylum species. The phylogenetic analysis strongly supported the genus Fagara as a subgenus of Zanthoxylum and proposed the possibility of a new subgenus in Zanthoxylum. The availability of these genomes will provide valuable information for identifying species, molecular breeding, and evolutionary analysis of Zanthoxylum.